Exceptionally large magneto-optical response in dispersions of plate-like nanocrystallites and magnetic nanoparticles - May, Kathrin; Eremin, Alexey; Stannarius, Ralf; Szabó, Balázs; Börzsönyi, Tamás; Appel, Ingo; Behrens, Silke; Klein, Susanne (Journal of magnetism and magnetic materials, 2017)
We introduce a binary colloidal system with an exceptionally strong magneto-optical response. Its induced optical birefringence at even low magnetic fields (in the mT range) reaches a value with the same order of magnitude as that of nematic liquid crystals. This system is based on a binary mixture of plate-like, non-magnetic pigment nanoparticles and a small volume fraction (<1v%) of spherical magnetic nanoparticles. In the field-free state, the suspension is isotropic. Birefringence is caused by an alignment of the pigment platelets, commanded by shape-anisotropic agglomerates of the magnetic nanoparticles in an external magnetic field. We give a semiquantitative discussion about this.